Perforation of the descending colon induced by alectinib in a patient with non-small cell lung cancer: a Case Report - Li, Yun; Yu, Ping; Wang, Ran (Frontiers in Pharmacology, 2025)
Anaplastic lymphoma kinase (ALK) inhibitor alectinib has demonstrated significant potential in treating non-small cell lung cancer (NSCLC); however, its adverse effects remain a notable challenge for healthcare professionals. This report examines the case of a 79-year-old female lung cancer patient who presented with persistent colic in the left abdomen 10 months after initiating alectinib treatment. Upon admission, abdominal computed tomography revealed mild thickening of the descending colon wall, accompanied by free gas and surrounding exudation, leading to a diagnosis of descending colon perforation. After excluding alternative causes of gastrointestinal perforation, the condition was attributed to a severe adverse reaction associated with alectinib. While alectinib has been reported to cause serious gastrointestinal perforations, the underlying mechanism remains unclear and warrants further clinical investigation. Clinicians should be vigilant in recognizing and promptly managing this potential complication during alectinib therapy.